Worldwide trends in mortality related to Parkinson's disease in the period of 1994–2019: Analysis of vital registration data from the WHO Mortality Database - Lampropoulos, Ioannis C.; Malli, Foteini; Sinani, Olga; Gourgoulianis, Konstantinos I.; Xiromerisiou, Georgia (Frontiers in Neurology, 2022)
Background: Τhe mortality from Parkinson’s disease (PD) and its long-term trends worldwide in recent decades remains unknown. No previous studies have simultaneously studied age- and sex-specific mortality trends at a population level worldwide. Insights gained from this study can help identify high-risk populations and inform healthcare service requirements for managing Parkinson’s disease globally. Objectives: To examine trends in mortality from Parkinson’s disease by age group and sex across countries all over the world. In this study, we used worldwide registry data to examine the temporal trends in PD mortality across most counties of the world from 1994 to 2019 using joinpoint regression. Results: In data from vital registration systems, huge variations in the patterns of deaths due to Parkinson’s disease were observed both over time and between countries. Between 1994 and 2019 there was a significant increase globally in mortality rates in both males and females. In more detail, mortality rate (per 100.000) in 1994 was 1.76 and reached 5.67 in 2019. Greater increases in mortality were seen in men compared to women; and in older than younger people. Conclusions: There has been a striking rising trend in Parkinson’s disease mortality globally. There are persistent age and sex disparities in Parkinson’s disease mortality trends. Our findings may have important implications for future research, healthcare planning, and provision.